Design and development of novel, short, stable dynorphin-based opioid agonists for safer analgesic therapy - Lohman, Rink-Jan; Reddy Tupally, Karnaker; Kandale, Ajit; Cabot, Peter J.; Parekh, Harendra S. (Frontiers in Pharmacology, 2023)
Kappa opioid receptors have exceptional potential as an analgesic target, seemingly devoid of many problematic Mu receptor side-effects. Kappa-selective, small molecule pharmaceutical agents have been developed, but centrally mediated side-effects limit clinical translation. We modify endogenous dynorphin peptides to improve drug-likeness and develop safer KOP receptor agonists for clinical use. Using rational, iterative design, we developed a series of potent, selective, and metabolically stable peptides from dynorphin 1-7. Peptides were assessed for in vitro cAMP-modulation against three opioid receptors, metabolic stability, KOP receptor selectivity, desensitisation and pERK-signalling capability. Lead peptides were evaluated for in vivo efficacy in a rat model of inflammatory nociception. A library of peptides was synthesised and assessed for pharmacological and metabolic stability. Promising peptide candidates showed low nanomolar KOP receptor selectivity in cAMP assay, and improved plasma and trypsin stability. Selected peptides showed bias towards cAMP signalling over pERK activity, also demonstrating reduced desensitisation. In vivo, 2 peptides showed significant opioid-like antinociception comparable to morphine and U50844H. These highly potent and metabolically stable peptides are promising opioid analgesic leads for clinical translation. Since they are somewhat biased peptide Kappa agonists they may lack many significant side-effects, such as tolerance, addiction, sedation, and euphoria/dysphoria, common to opioid analgesics.